MELACAK TEKS-TEKS HIPOGRAM DALAM NOVEL LARUNG KARYA AYU UTAMI - Wiyatmi Wiyatmi (Jurnal Penelitian Humaniora, 2003)
Abstract This research is aimed at finding and understanding the texts of hypogram in a novel entitled Larung and explaining the form of transformation and function in the novel. The achieved those aim the novel is read repeatedly. Some texts, assumed as hypogram and having intertextual relation with the novel, are identified. The texts, then are studies. The similarities and differences between the texts and the novel are examined. In the frame of literary reception the data is studied to explain the relation between the texts of hypogram and the novel. The results of research show there are five texts of hypogram having intertextual relation with the novel and becoming the background of the novel. The five texts are Calon Arang, Wayang Purwa(particularly in relation to the characters of Wisanggeni, Shakuntala, Togog, Bilung, dan Durga), children’s song “Kupu-kupu yang Lucu”, children’s story Puss in Boots (Kucing Bersepatu), and novel Histoire d’O. In Larung those five texts of hypogram are in the form of pastiche and parody. The form of pastiche  is because of no significant change in the essence between the texts and the novel, while the forms of parody is because thereis significant change of meaning between the texts and the novel. In Larung the texts of hypogram function to integrally build structures of characters and story because the texts become the model of names, characterization, plot and setting. The result shows that there is an inseparable relation between contemporary and old literary texts. In content of literary reception and postmodern aesthetics a text basically a mosaic of quotations. Keywords: Larung, hypogram, intertextual